The decline in muscle strength and muscle quality in relation to metabolic derangements in adult women with obesity. Issue 5 (October 2019) - Poggiogalle, Eleonora; Lubrano, Carla; Gnessi, Lucio; Mariani, Stefania; Di Martino, Michele; Catalano, Carlo; Lenzi, Andrea; Donini, Lorenzo Maria
Summary: Background & aims: The metabolic and functional characteristics related to sarcopenic obesity have not been thoroughly explored in the earlier stages of the aging process. The aim of the present study was to examine the phenotype of sarcopenic obesity, in terms of lean body mass, muscle strength and quality, in adult women with and without the Metabolic Syndrome (MetS), and its relationship with the features of myosteatosis. Methods: Study participants were enrolled at the Sapienza University, Rome, Italy. Body composition was assessed by DXA. The Handgrip strength test (HGST) was performed. HGST was normalized to arm lean mass to indicate muscle quality; intermuscular adipose tissue (IMAT) and intramyocellular lipid content (IMCL) were measured by magnetic resonance imaging and spectroscopy, as indicators of myosteatosis. Different indices of sarcopenia were calculated, based on appendicular lean mass (ALM, kg) divided by height squared, or weight. The NCEP-ATPIII criteria were used to diagnose the MetS. HOMA-IR was calculated. The physical activity level (PAL) was assessed through the IPAQ questionnaire. Results: 54 women (age: 48 ± 14 years, BMI: 37.9 ± 5.4 kg/m 2 ) were included. 54% had the MetS (metabolically unhealthy, MUO). HGST/arm lean mass was lower in MUO women than women without the MetS (6.3 ± 1.8 vs. 7.8 ± 1.6, p = 0.03). No differences emerged in terms of absolute ALM (kg) or other indices of sarcopenia (ALM/h 2 or ALM/weight) between metabolically healthy (MHO) vs. MUO women (p > 0.05). Muscle quality was negatively associated with HOMA-IR (p = 0.02), after adjustment for age, body fat, hs-CRP levels, and PAL. IMAT, but not IMCL, was significantly higher in obese women with the MetS compared to women without the MetS (p > 0.05). No association emerged between HGST/arm lean mass and IMAT or IMCL when HOMA-IR was included in the models. Conclusion: Insulin resistance, and not sarcopenia or myosteatosis per se, was associated with muscle weakness, resulting in the phenotype of "dynapenic obesity" in middle-aged women with the metabolic syndrome.